INCREASE IN QTC DISPERSION PREDICTS ARRHYTHMIC EVENTS IN PATIENTS WITH CARDIAC RESYNCHRONIZATION THERAPY - Cuneyt Kocas; Okay Abaci; Kadriye Orta Kilickesmez; Ferid Aliyev; Yusuf Atayev; Cengizhan Yusuf; Cengiz Celiker (Российский кардиологический журнал)
Aim. Benefits of CRT on mortality and morbidity in patients with severe CHF are clear but the effect of CRT on sudden cardiac death is more controversial. It has been suggested that CRT may catalyze arrhythmogenicity by reversing the normal depolarization pattern. The purpose of this study was to examine the effect of CRT on dispersion of repolarization as assessed by ECG. We also sought to determine the value of dispersion of repolarization ECG parameters in predicting the occurrence of major arrhythmic events (MAE) in follow-up.Material and methods. A total of 48 patients with end-stage heart failure and QRS duration >120 ms underwent CRT. QT dispersion (QTd), T peak t end interval (Tpe) and T peak t end dispersion (Tpe dispersion) were measured before and immediately after CRT implantation. All patients were followed at least 12 months for ventricular tachycardia or fibrillation that were treated with antitachicardia pace or cardioversion.Results. Over 16±7.1 months, 14 patients had a MAE. Compared to baseline, after CRT, QTc dispersion (84.66±37.7 vs 100.36±47.4, p=0.04) and Tpe interval (104.1±20.4 vs 122.03±33, p=0.02) increased significantly. Increase in QTD (ΔQTD) (31.66±39.5 vs 5.57±5.59, p=0.03), and QTc dispersion (ΔQTc dispersion) (40.19±46.6 vs 4.39±14.35, p=0.04) from baseline was signifcantly higher in MAE group. In multiple regression analyses, ΔQTc dispersion predicted MAE (p=0.045, CI: 1.000–1.033).Conclusion. Immediately after CRT implantation QTc dispersion and Tpe interval increases and increase in QTc dispersion predicts MAE in one year follow up.